APPLICATION OF RESTORATIVE JUSTICE TO FAMILY VIOLENCE CRIMES - Sumarno, Sumarno; Syahranuddin, Syahranuddin (Proceeding International Seminar of Islamic Studies, 2023)
The application of restorative justice in efforts to resolve criminal acts of violence in the family is an effort in law enforcement solutions and can act as a mediator in bridging victims and perpetrators to reach solutions in unraveling problems that occur in domestic life. The application of the law through criminal proceedings is carried out if no agreement is reached between the parties as victims and perpetrators. Restorative justice has not been specifically regulated in the provisions of the law, but is an alternative way to solve problems, especially the resolution of domestic violence. The Law on the Elimination of Domestic Violence in reality is a hope in solving the occurrence of domestic violence which in its resolution is very complex and involves various parties in solving social problems and their diversity that occur in community life. It is expected that the government will be more assertive in terms of carrying out its duties and authorities in accordance with the law and indiscriminately in decision-making, firm action in solving problems that occur within the household is a natural thing in providing services to the community in determining the final choice in solving problems faced by each individual.